2016
DOI: 10.3390/su8050410
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of the CaCl2 Mass Fraction on the Efficiency of a Heat Pump Integrated Heat-Source Tower Using an Artificial Neural Network Model

Abstract: An existing idle cooling tower can be reversibly used as a heat-source tower (HST) to drive a heat pump (HP) in cold seasons, with calcium chloride (CaCl 2 ) aqueous solution commonly selected as the secondary working fluid in an indirect system due to its good thermo-physical properties. This study analyzed the effect of CaCl 2 mass fraction on the effectiveness (ε) of a closed HST and the coefficient of performance (COP) of a HP heating system using an artificial neural network (ANN) technique. CaCl 2 aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Control strategy is very important in improving the performance of a heat pump [8]. Wei et al [17] used the Artificial Neural Network (ANN) model for predicting the performance of the Heat Pump (HP). Their study indicated that the ANN model was reliable and robust.…”
Section: Introductionmentioning
confidence: 99%
“…Control strategy is very important in improving the performance of a heat pump [8]. Wei et al [17] used the Artificial Neural Network (ANN) model for predicting the performance of the Heat Pump (HP). Their study indicated that the ANN model was reliable and robust.…”
Section: Introductionmentioning
confidence: 99%
“…The three-layer ANN model has been used in the prediction of HP system performance. The study depicted that the application of ANN in the prediction of the HP system was consistent and robust [14]. Yang et al [15] have used a simultaneous control strategy to improve the precision of drying temperature and superheat.…”
Section: Introductionmentioning
confidence: 90%
“…The system, located on the rooftop of a single-story building at Hunan University of China, was originally designed as a heating source for hot water supply [12,27]. As shown in Figure 3a, the closed wet cooling tower was an induced draft counter-flow type and specially designed, and Figure 3b showed that the heat pump system was an integrated water-to-water HP unit with a rated power of 3.1 kW and a total cooling capacity of 15.3 kW.…”
Section: Methodsmentioning
confidence: 99%